2007
DOI: 10.1002/masy.200751108
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Model for the Kinetics of Crystallization in Crystaf

Abstract: Summary: A series of ethylene homopolymers and ethylene/1-hexene copolymers with different molecular weight distributions (MWD) and chemical composition distributions (CCD) was analyzed by crystallization analysis fractionation (Crystaf) at several cooling rates to investigate the effect of MWD, CCD, and cooling rate on their Crystaf profiles. Using these results, we developed a mathematical model for Crystaf that considers crystallization kinetic effects ignored in all previous Crystaf models and can fit our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 17 publications
(26 reference statements)
6
34
0
Order By: Relevance
“…[ 15 ] Similar trends also observed in both CRYSTAF and TREF models. [10][11][12][13][14] The parameter n was also found to be constant at 4.5, which is close to the Avrami exponent in CRYSTAF and TREF models ( n ≈ 4.49) as well. The values of parameter k were strongly infl uenced by the cooling rate, the k value increases with an increase in the cooling rate; this has also been observed in CRYSTAF and TREF models.…”
Section: Effect Of Elution Flow Ratementioning
confidence: 95%
See 1 more Smart Citation
“…[ 15 ] Similar trends also observed in both CRYSTAF and TREF models. [10][11][12][13][14] The parameter n was also found to be constant at 4.5, which is close to the Avrami exponent in CRYSTAF and TREF models ( n ≈ 4.49) as well. The values of parameter k were strongly infl uenced by the cooling rate, the k value increases with an increase in the cooling rate; this has also been observed in CRYSTAF and TREF models.…”
Section: Effect Of Elution Flow Ratementioning
confidence: 95%
“…[10][11][12][13][14][15] The modeling approach based on crystallization kinetics and the concept of population balances was fi rst introduced to describe CRYSTAF. [10][11][12][13] Although TREF differs from CRYSTAF, the concept of population balances can be adapted to TREF by discretizing the TREF columns in a series of small control volumes. A TREF model based on crystallization/dissolution kinetics and population balances was successfully used to describe the TREF analysis of ethylene/1-olefi ns with various chain microstructures at a wide range of operating conditions.…”
Section: Discretizationmentioning
confidence: 99%
“…They have shown that the absolute crystallinity decreases with increasing comonomer content and vice versa. Soares et al [63] analyzed a series of ethylene homopolymers and ethylene/1-hexene copolymers with different molar masses and chemical composition distributions by CRYSTAF at several cooling rates. The effects of MMD, CCD and cooling rates on the CRYSTAF profiles were investigated.…”
Section: Crystallization Analysis Fractionationmentioning
confidence: 99%
“…LLDPEs with elevated comonomer content are unable to crystallize in the presence of a good solvent, like 1,2,4‐trichlorobenzene or orthodichlorobenzene. Co‐crystallization further complicates the separation of multiple‐component systems with poor precision and accuracy . Therefore, thermal gradient interaction chromatography (TGIC) has been adapted in order to determine the chemical composition of polyolefins .…”
Section: Introductionmentioning
confidence: 99%